Comprehensive insights into the disease burden linked to air pollution exposure across U.S. states: findings from the 2021 Global Burden of Disease Study - Lin, Kaibin; Quan, Junxian; Liao, Jiafen; Chen, Yiyue; Zhou, Bing; Xu, Xi (Frontiers in Public Health, 2025)
BackgroundAmbient air pollution persists as a critical global health threat, ranking fourth among risk factors for premature mortality. Despite decades of air quality improvements in the U.S. through regulatory measures, persistent health impacts remain, driven primarily by particulate matter (PM2.5) and ozone.ObjectiveThis study aimed to quantify long-term trends (1990–2021) in air pollution-attributable disease burdens across U.S. states, evaluate the effectiveness of existing policies, and identify priorities for future public health strategies to address persistent and emerging risks.MethodsUsing the Global Burden of Disease (GBD) 2021 dataset, we analyzed age-standardized mortality, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs) attributable to PM2.5, ozone, and household air pollution. Disease burdens were assessed for chronic obstructive pulmonary disease (COPD), diabetes mellitus, ischemic heart disease (IHD), lower respiratory infections, stroke, and lung cancer. Data were standardized to the GBD reference population for comparability over time.ResultsFrom 1990 to 2021, PM2.5-attributable mortality declined by 80.5%, with IHD deaths falling by 70.6% (79,684–23,433 deaths) and associated DALYs by 71.2%. However, diabetes-related YLDs surged 97.4% nationally, reflecting interactions with obesity and lifestyle factors. Formerly high-pollution states (e.g., Indiana, Tennessee) achieved substantial (30%−40%) reductions in PM2.5-linked DALYs for IHD and COPD, while California saw a 12.3% rise in diabetes DALYs. In 2021, residual burdens disproportionately affected older adults and males, with IHD mortality rates 1.8 times higher in men. Ozone-related COPD deaths showed minimal decline despite falling ozone levels.